Networks, stocks, and climate change: A new approach to the study of foreign investment and the environment. (May 2022) - Jorgenson, Andrew; Clark, Rob; Kentor, Jeffrey; Rieger, Annika
Abstract: This study offers a new approach to the study of foreign direct investment (FDI) and the environment. We argue that both the accumulation of inward FDI and a nation's position in the global network of FDI could facilitate either environmentally beneficial spillover effects and technology transfers or the outsourcing and distancing of environmentally harmful and ecologically unsustainable economic activities. In other words, the environmental impacts, good or bad, are potentially greater for nations that occupy more central positions in the world's FDI network and for nations with relatively larger amounts of inward FDI. To test these arguments, we estimate cross-national longitudinal models of total carbon dioxide emissions and carbon dioxide emissions per unit of GDP. The results suggest that both emissions outcomes are positively associated with inward FDI stocks and FDI network centrality for the overall sample of nations, but these positive associations are much more pronounced for Global South nations than for Global North nations. Overall, the findings are consistent with the arguments that foreign investment facilitates the outsourcing of energy inefficiency and environmentally harmful production processes, leading to growth in fossil-fuel consumption and concomitant carbon emissions for receiving nations, especially in the Global South. We conclude by summarizing the limitations of our analysis, and outline some next steps for this new approach to the study of FDI and the environment.